Contrasting effects of singlet oxygen and hydrogen peroxide on bacterial community composition in a humic lake - Glaeser, Stefanie P.; Berghoff, Bork A.; Stratmann, Verena; Grossart, Hans-Peter; Glaeser, Jens; Justus Liebig University Giessen (My University, 2014)
Light excitation of humic matter generates reactive oxygen species (ROS) in surface waters of aquatic ecosystems. Abundant ROS generated in humic matter rich lakes include singlet oxygen (1O2) and hydrogen peroxide (H2O2). Because these ROS differ in half-life time and toxicity, we compared their effects on microbial activity (14C-Leucine incorporation) and bacterial community composition (BCC) in surface waters of humic Lake Grosse Fuchskuhle (North-eastern Germany). For this purpose, experiments with water samples collected from the lake were conducted in July 2006, September 2008 and August 2009. Artificially increased 1O2 and H2O2 concentrations inhibited microbial activity in water samples to a similar extent, but the effect of the respective ROS on BCC varied strongly. BCC analysis by 16S rRNA gene clone libraries and RT-PCR DGGE revealed ROS specific changes in relative abundance and activity of major bacterial groups and composition of dominating phylotypes. These changes were consistent in the three experiments performed in different years. The relative abundance of Polynucleobacter necessarius, Limnohabitans-related phylotypes (Betaproteobacteria), and Novosphingobium acidiphilum (Alphaproteobacteria) increased or was not affected by photo-sensitized 1O2 exposure, but decreased after H2O2 exposure. The opposite pattern was found for Actinobacteria of the freshwater AcI-B cluster which were highly sensitive to 1O2 but not to H2O2 exposure. Furthermore, group-specific RT-PCR DGGE analysis revealed that particle-attached P. necessarius and Limnohabitans-related phylotypes exhibit higher resistance to 1O2 exposure compared to free-living populations. These results imply that 1O2 acts as a factor in niche separation of closely affiliated Polynucleobacter and Limnohabitans-related phylotypes. Consequently, oxidative stress caused by photochemical ROS generation should be regarded as an environmental variable determining abundance, activity, and phylotype composition of environmentally relevant bacterial groups, in particular in illuminated and humic matter rich waters.
Keywords: ddc:570